Justice in Inheritance Distribution: Comparative Study of Islamic and Customary Law on Equal Distribution - Nugraha, Iqbal Subhan (Sharia Journal and Education Center Publishing, 2024)
This study discusses the acceptance of the practice of equal distribution of inheritance in Indonesia, with the aim of analyzing how the principle of justice is applied in a changing social context. In this study, a normative juridical approach is used to examine relevant legal texts and literature, including the Qur'an, hadith, and the views of scholars on inheritance. The results of the study show that although urban and educated communities show support for the fair distribution of inheritance, the traditional interpretation of sharia that is still held by some scholars often hinders the application of the principle of gender justice in the distribution of inheritance. This study also found that there is a shift in values in society that is increasingly open to gender equality, but is still hindered by sharia normative provisions. The conclusions of this study emphasize the need for a more flexible approach in the interpretation of inheritance law by scholars and community leaders, as well as the push for more inclusive and adaptive regulatory reforms to the needs of modern society. Thus, this research makes a significant contribution to the development of Islamic legal theory and social justice, as well as encourages a broader dialogue on inheritance law reform in Indonesia. This finding is expected to be a reference for further studies and policy-making that are more responsive to the issue of gender equality in inheritance practices.